2015
DOI: 10.1159/000381008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Indoxyl Sulfate Dialyzer Clearance with the Use of Binding Competitors

Abstract: Background: Indoxyl sulfate is a protein-bound uremic toxin and its dialytic clearance is comparatively low. We propose a method to increase indoxyl sulfate dialytic clearance. Methods: Human serum albumin, preloaded with indoxyl sulfate, was circulated on the blood side of an F40S dialyzer with single-pass counter-current dialysate flow. Tryptophan or docosahexaenoic acid (DHA), which are binding competitors to indoxyl sulfate, were infused into the blood-side circuit upstream of the dialyzer, and their abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…The added convective component of hemodiafiltration adds only little beyond the PBUT removal achieved in standard high-flux HD 13 , 14 . Additional approaches to remove PBUTs also exist, notably (i) adsorption of toxins during dialysis on mixed-matrix membranes 15 or on adsorbent zeolite silicalite 16 , (ii) maintaining the diffusive gradient across the dialyzer fiber by circulating albumin 17 or activated charcoal in the dialysate 18 , (iii) displacing PBUTs from albumin using binding competitors to increase the free toxin fraction 19 , 20 , and (iv) weakening the toxin affinity for albumin using a high-frequency electromagnetic field 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The added convective component of hemodiafiltration adds only little beyond the PBUT removal achieved in standard high-flux HD 13 , 14 . Additional approaches to remove PBUTs also exist, notably (i) adsorption of toxins during dialysis on mixed-matrix membranes 15 or on adsorbent zeolite silicalite 16 , (ii) maintaining the diffusive gradient across the dialyzer fiber by circulating albumin 17 or activated charcoal in the dialysate 18 , (iii) displacing PBUTs from albumin using binding competitors to increase the free toxin fraction 19 , 20 , and (iv) weakening the toxin affinity for albumin using a high-frequency electromagnetic field 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, de Loor et al observed that when sodium octanoate (a medium chain fatty acid characterized as a binding competitor) was added to normal and uremic serum, p‐CS, and IS were inhibited to bind HSA. Moreover, Tao et al revealed that 0.6 μmol/min of DHA increased IS removal by 25% in an in vitro HD model. The authors therefore argued that protein‐binding competitors may be a new strategy to improve the removal of uremic toxins with HD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dialysis techniques have been investigated to improve the quality of life of HD patients, and the current focus has been on ways to increase the clearance rate of protein‐bound uremic toxins. Thus far, new techniques based on a longer time for HD, a higher dialysate flow rate and other factors have increased the clearance rate by no more than 1.5 times that of traditional HD, which has a plasma removal rate of IS and p‐CS of approximately 7% …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another area of research concerns altering the dialysis milieu in order to affect the binding of URS to plasma proteins. Examples of this effort which have data supporting their use include using hypertonic solution, the use of albumin-binding site competitors such as tryptophan and docosahexaenoic acid, increasing temperature, plasma dilutions, and pH manipulation of the dialysate [47,[90][91][92][93][94].…”
Section: Dialysismentioning
confidence: 99%